Comparing KTP and CO2 laser excision for recurrent respiratory papillomatosis: A systematic review - Jimin Yang; Zhongcheng Xie; Barnabas C. Seyler (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective The CO2 laser and 532 nm potassium titanyl phosphate (KTP) laser have been applied to treat recurrent respiratory papillomatosis (RRP). This systematic review sought to compare outcome differences between these two methods. Data Sources Embase, Web of Science, PubMed, and the Cochrane Library. Review Methods CO2 laser and KTP laser studies were obtained by keyword searches of four authoritative medical databases. Articles were screened and retained when conforming to inclusion criteria. The primary outcome was cure rate; the secondary outcomes were recurrence, death, remission, clearance, and human papillomavirus (HPV)‐detected rates, as well as laser effectiveness rates. Postoperative complications rate was the safety outcome measure. All outcomes were summarized within the CO2 and KTP groups, with results statistically compared (p < .05). Results Overall, the cure rates were 87.25% (KTP group) and 75.98% (CO2 group; p < .05). Complication rates significantly differed between the KTP (2.32%) and CO2 (17.71%) groups (p < .0001). There was a relatively higher but not significant difference in the recurrence rates between the CO2 (18.6%) and KTP (10.87%) groups (p = .1595). The CO2 group remission rate was considerably lower (38.9%) than the KTP group (88.46%, p < .0001). HPV‐detected and clearance rates were only reported for the CO2 group. The bias risks were 13.1 ± 1.45 (CO2) and 13.6 ± 1.52 (KTP) for the two groups, indicating evidence was of fair quality. Conclusion Overall, KTP laser excision showed significantly better postoperative clinical outcomes than the CO2 laser, with a lower failure rate. Available fair‐quality evidence suggests KTP laser excision might be better for treating RRP. Nevertheless, more high‐quality randomized controlled studies are needed to compare these two surgical techniques, particularly in terms of reporting functional data such as vocal outcomes.